Games in Acquiring First and Second Language Skills - Leztiyani, Indirawati; Nuryani, Nuryani (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
Humans are born with tremendous potential in the ability to think. The development of this thinking is a gradual process, with the most critical period occurring during childhood, often referred to as "The Golden Age" During this time, the ability to think develops rapidly, but keep in mind that this development must be maintained so that it is not inhibited or atrophied. In the early stages of a child's thinking development, the most striking abilities are speech and walking. Speaking, in particular, is heavily influenced by the environment and the role of parents in shaping the child's first language. A child's second language, on the other hand, is often acquired during the school years with the guidance of teachers. To develop first and second language skills, games are an effective and fun method. Games such as drawing, singing, word scramble, gardening, word puzzles, finding missing letters, counting and storytelling can be used. After analyzing various games by involving parents and teachers as assessment subjects, it was found that counting and singing games are very effective and preferred. Both games provide many benefits, including ease of implementation, motor development, increased thinking power, child confidence, and support from various musical and mathematical instruments. The counting and singing games can also be adapted to different languages, which supports children in their learning.